WACANA INTERAKTIF KELAS ANTARA GURU DAN SISWA KELAS 1,2,3 SEKOLAH DASAR DALAM PROSES PEMBELAJARAN TEMATIK - Siti Wachidah, (Pendidikan Dasar, 2010)
Abstract; The discourse analysis aims to identify the interactive pattern in the teacher-led classroom spoken interaction in three thematic-based classes of the early level of elementary school, in terms of the moves, the speech roles, and the speech acts. The theoretical framework for this paper finds support in Vygotskys and Hallidays language-based theory of intellectual development. The results indicate an equally highly teacher-centered pattern of interaction in the three classes, hence severely limited opportunity for students to participate in meaning-making activities. It is argued that improved learning opportunity in the thematic-based lesson would result from improve quantity and quality of students speech roles and speech acts.